The Properties Of Lightweight Foamed Mortar (LFM) Incorporating With Oil Palm Empty Fruit Bunch (EFB) Fibre - Musa, Mazlina (2019)
The key players in the construction industry around the globe are very enthusiastic in producing better construction materials that are cost-effective, durable, lightweight and long lasting without jeopardizing the environment. One of the best ways in producing such building materials are by incorporating industrial waste materials such as Empty Fruit Bunch (EFB) fibre in Lightweight Foamed Mortar (LFM).